Eco-friendly sol-gel derived sodium-based ormolytes for electrochromic devices - Fernandes, M. (2017)
The sol-gel method was employed in the preparation of a novel range of organicinorganic biohybrid electrolytes composed of a di-urethane cross-linked poly(ε- caprolactone) (PCL(530) chains/siloxane doped with different amounts of sodium triflate (NaCF3SO3.xH2O). The samples are semi-crystalline and thermally stable up to ca. 250 ºC. The maximum ionic conductivity (4.1 × 10-7 , 1.5 × 10-4 and 8.8 × 10-4 S cm-1 at 30, 49 and 97 º C, respectively) was attained at n = 6, where n (composition) corresponds to the number of (C(=O)(CH2)5O) repeat units of PCL(530) per sodium ion.(não se fala do U(600)…foram usadas amostras já sintetizadas?) Selected ormolytes were employed in the construction and characterization of prototypes electrochromic devices (ECDs). Tests with prototype ECDs were very promising. The devices exhibited fast switching time of ca. 30 s. The performance of the devices depended on the nature of the host matrix and salt concentration. The ECD@U60063Na device exhibited the highest Δ(OD)555 nm value (0.12) and bleaching coloration efficiency (CEout = 131 mC cm-2 , 555 nm, 50th cycle) and good optical memory effect. The ECD@PCL58Na device exhibited a coloring coloration efficiency (CEin 108 mC cm-2 , 555 nm, 50th cycle) similar to that of ECD@U60063Na (CEin 116 mC cm-2 , 555 nm, 50th cycle) and a very good stability.